Comment on “The influence of Mencius’ humanism and benevolent government on contemporary society” - Sun, Jingyang (2025)
Commented article: YANG, Qiong. The Influence of Mencius’ Humanism and Benevolent Government on Contemporary Society. Trans/Form/Ação: Unesp Journal of Philosophy, v. 47 n. 4, e0240083, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/14844.